Transformasi Agrokompleks Menuju Ekonomi Sirkular Peluang dan Tantangan Implementasi di Indonesia - Annisa, Istiqama Maulidina (Journal of Agro Complex Development Society, 2025)
This study critically examines the transformative potential of circular economy principles within Indonesia's agrocomplex sector, an imperative shift given the agricultural sector's 13% contribution to the national GDP and employment of 29% of the workforce. Through a mixed-method approach incorporating in-depth interviews with 35 key stakeholders across five major Indonesian regions, focus group discussions, and system dynamics modeling, the research identifies significant opportunities for resource optimization where 63.7% of agricultural biomass currently remains unutilized or burned. The study uncovers five promising circular business models: Industrial-Agricultural Symbiosis, Agricultural Resource Sharing Platforms, Distributed Biorefinery, Product-as-a-Service Agriculture, and Regenerative Supply Chains, with Industrial-Agricultural Symbiosis demonstrating the highest benefit-cost ratio of 3.7 and potential carbon emission reductions of 42%. Key implementation enablers include supportive policies, access to green financing, technological capacity, multi-stakeholder collaboration, and capacity development, while primary barriers encompass value chain fragmentation, infrastructure limitations, inadequate economic incentives, resistance to change, and capacity constraints. A strategic three-phase roadmap (2025-2035) is proposed to accelerate the transition toward a circular agrocomplex in Indonesia, requiring an estimated investment of Rp156.3 trillion over a decade with potential to create 4.4 million new jobs. The findings emphasize the importance of integrating traditional agricultural wisdom with modern technology and establishing collaborative governance frameworks to ensure an equitable distribution of benefits throughout the agricultural value chain, ultimately redefining the relationship between production, consumption, and regeneration in Indonesia's food system.